ANALISA PENGARUH INFLASI & GDP (GROSS DOMESTIC PRODUCT) TERHADAP ROAA (RETURN ON AVERAGE ASSETS) PADA 10 BANK DENGAN KATEGORI ASET TERBESAR DI INDONESIA PERIODE 2005-2008 - Arif Prawira; Arnold Japutra (Universitas Bunda Mulia, 2017)
The background of this research is the phenomenon of global crisis began with Subprime Mortgage in America which make lots of company in finance get loss and a lot of them must be closed because of bankruptcy. The purpose of this research is to know the implication of macroeconomic especially inflation and GDP (Gross domestic Product) to ROAA (Return on Average Assets) in banking. The subject of this research is the ten biggest banks in category of asset in Indonesia. The object of this research is financial statements of the ten biggest banks in category of asset in Indonesia, GDP Indonesia and inflation in research’s period. The result of this research are with level of confidence 95%, inflation has not significant impact to ROAA while GDP was controlled and GDP has not significant impact to ROAA while inflation was controlled. Keyword : ROAA, Inflation, GDP